Tussen verbeelding en macht : 25 jaar nieuwe sociale bewegingen in Nederland - Duyvendak, J.W.; van der Heijden, Hein-Anton; Koopmans, Ruud (Amsterdam : SUA, 1992)
Fonds Suzan Daniel (FSD)
Nederlands
Monografie